The evaluation and measurement of library services - Matthews, Joseph R. (Libraries Unlimited, 2007)
Matthews outlines and argues for a broader and more robust adoption of evaluation techniques in order to help library managers combine traditional internal measurements with more customer-centric measurements to form a truer picture of a library's value for its stakeholders and patrons.